Oral manifestations in 101 Cambodian - C. Bendick,C. Scheifele2,P. A. Reichart2 (Blackwell Synergy)
The general health status of 101 Cambodian patients with HIV infection and AIDS was poor, and they demonstrated a large number of oral manifestations. Antiretroviral therapy is presently not available and only a fraction of patients receives antimycotic treatment (25.7%). HIV infection and the AIDS epidemic in Cambodia have become a serious problem and patients urgently need adequate diagnosis and antiretroviral therapies.